2022
DOI: 10.3390/app12146869
|View full text |Cite
|
Sign up to set email alerts
|

Incident Angle Dependence of the Waveform of the Polarization-Sensitive Photoresponse in CuSe/Se Thin Film

Abstract: The results of studying the waveforms of longitudinal and transverse photocurrent pulses generated in thin, semitransparent CuSe/Se films as a function of the angle of incidence (α) of a femtosecond laser beam at linear and circular polarizations are presented. It has been established that the durations of unipolar longitudinal photocurrent pulses at linear and circular polarizations of laser pumping do not depend on the angle α. It is shown that the evolution of the temporal profile of the helicity-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In [9], the generation of nanosecond photocurrent pulses due to the surface photogalvanic effect (the second-order nonlinear optical phenomenon) was studied in thin semitransparent CuSe/Se films as a function of the angle of incidence and polarization of exciting femtosecond laser pulses at 795 nm. It was found that the evolution of the temporal profile of the helicity-sensitive transverse photocurrent with a change in incident angle strongly depends on polarization.…”
Section: Summary Of the Articles Of The Issuementioning
confidence: 99%
“…In [9], the generation of nanosecond photocurrent pulses due to the surface photogalvanic effect (the second-order nonlinear optical phenomenon) was studied in thin semitransparent CuSe/Se films as a function of the angle of incidence and polarization of exciting femtosecond laser pulses at 795 nm. It was found that the evolution of the temporal profile of the helicity-sensitive transverse photocurrent with a change in incident angle strongly depends on polarization.…”
Section: Summary Of the Articles Of The Issuementioning
confidence: 99%
“…However, we have recently observed SPGE photocurrent generation in thin CuSe and CuSe/Se films upon excitation by femtosecond laser pulses. [ 48,49 ] Meanwhile, according to, [ 25,40,41 ] in the generation of surface photocurrent in the metal and metal–semiconductor nanocomposite films, PDE and SPGE manifest simultaneously. In contrast to volumetric metal samples, [ 25 ] the SPGE and PDE signals in the films with moderate sheet resistance are significant and can be observed at room temperature.…”
Section: Introductionmentioning
confidence: 99%